(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2009)
Este artigo averigua algumas especificidades da formação industrial do Estado do Paraná no período de 1920 a 2000. A análise foi dividida em duas etapas: antes e depois de 1970, pois após 1970 o Paraná passou por profundas transformações estruturais na sua economia. Antes de 1970, os ciclos produtivos da economia paranaense foram agrícolas. Desses ciclos, a expansão da produção de café na região Norte do Paraná contribuiu mais significativamente na economia e no comportamento populacional. Após 1970, o Paraná cresceu e desenvolveu-se devido à modernização da agropecuária e ao processo de desconcentração industrial ocorrido no Brasil. O resultado foi a passagem de uma economia primária exportadora para uma economia baseada na transformação agroindustrial e industrial moderna. This article investigates some specificities of the industrial formation of the State of Paraná (Brazil) from 1920 to 2000. The analysis was divided into two stages: before and after 1970, for after 1970 the State of Paraná underwent deep structural transformations in its economy. Before 1970 the productive cycles of the economy of the State of Paraná had an agricultural character. Among these cycles, the expansion of the coffee production in northern Paraná contributed more significantly to the economy and the behavior of the population. After 1970, the State of Paraná underwent a process of development due to the modernization of farming procedures and to the process of industrial diffusion that took place in Brazil. The result was the shift from a primary economy based on exportation to an industrial economy based on modern agribusiness and industrial transformation. Key words: regional economy, economic history, industrial economy